2017
DOI: 10.1111/anae.13787
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided approach to nerves (direct vs. tangential) and the incidence of intraneural injection: a cadaveric study

Abstract: This study evaluated the incidence of nerve puncture and intraneural injection based on the needle approach to the nerve (direct vs. tangential). Two expert operators in regional anaesthesia performed in-plane ultrasound-guided nerve blocks (n = 158) at different levels of the brachial plexus in cadavers, aiming either directly for the nerve (n = 77) or tangentially inferior to the nerve (n = 81). After reaching the outer limit of the nerve, the needle was intentionally advanced approximately 1 mm in both appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…We appreciate Szerb and Kwesi Kwofie's comments on our recent paper [1]. We would like to emphasise that our study was a simulation of inadvertent needle advancement and subsequent injection, and does not reflect the needle approach used in clinical practice.…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate Szerb and Kwesi Kwofie's comments on our recent paper [1]. We would like to emphasise that our study was a simulation of inadvertent needle advancement and subsequent injection, and does not reflect the needle approach used in clinical practice.…”
Section: A Replymentioning
confidence: 99%
“…Ultrasound-guided block and the incidence of intraneural injection Sermeus et al suggested that a tangential approach to needle/nerve contact "should be included in algorithms for performing peripheral nerve block in order to prevent puncture and intraneural injection" [1]. We share their concerns with regard to the risk of inadvertent needle trauma and intraneural injection, and would like to invite the authors to reply to some observations we have about their study.…”
mentioning
confidence: 94%
“…In a cadaver study of upper extremity blocks administered under ultrasound guidance, Sermeus et al [17] found the incidence of intraneural injection higher in procedures performed with a direct approach with ultrasonographic guidance to the target nerve compared to those performed with a tangential approach. In the current study, the possibility of needle contact with the brachial plexus was increased in Group 2, where local anesthetic agents were administered at 2, 6 and 9 o'clock levels of the subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Vários outros modelos já foram relatados como o uso de água e gelatina/ágar 9 , Blue Phantom™ 10 e os moldes que utilizam produtos orgânicos, como modelo animal 6,7 . Por outro lado, para ser considerado ideal, o simulador de ultrassom deve possuir a ecogenicidade comparável a dos tecidos humanos 6,7,9 , estar rapidamente disponível 7 , ter baixo custo 6 , possibilidade de ser utilizado repetidamente 6,7,9,10 , promover um feedback tátil 6,7,9 , manter a agulha estática 6,7,9,10 , não deixar evidente o caminho da agulha e não causar exposição a agentes nocivos à saúde 6,7,9,[10][11][12][13] . Todas essas características puderam ser observadas no modelo proposto com adaptação de gel balístico.…”
Section: Discussionunclassified